Inadequate Quality Research Outputs from Homoeopathic Colleges in India: Why? (Homoeopathy for All, 2025)
Introduction There are about 103 undergraduate and 57  postgraduate homoeopathic medical colleges  in India, permitted by National Council for  Homoeopathy (NCH), for admission during  the sessions 2024-25 & 2025-26. Having the  largest infrastructure in terms of colleges,  in comparison to other countries, their  contributions in the field of research are not so  much encouraging. If we meticulously analyse  different factors behind such inadequate  research outputs, the following issues will  generally come to our minds, which are  discussed below. Problems related to the faculty 1 Lack of aptitude for research among faculty  members There is lack of aptitude or interest  for research among large number of  faculty members of homoeopathic  institutions. This issue can stem from  various factors, including heavy workloads,  lack of trainings, and a perception that  research is not valued as highly as other  academic duties. Addressing this issue  requires institutional support, including  dedicated time for research, mentorship  opportunities, and recognition for research  contributions. It requires motivation  by the management and support from  competent authorities to enhance vision  for research. Due to absence of provision  of incentives for conducting research and  inadequate research orientation among the  faculties, there is set back to research in  the premises of homoeopathic colleges.  2 Lack of mandatory research publication  for teaching faculty: It can lead to a decline  in academic engagement and research  output, potentially fostering complacency.  Research publication is crucial for  professional development, maintaining  academic rigor, and contributing to  the broader body of knowledge. But  publication of research studies, not  being compulsory for the teaching  faculty for their promotions & career  advancements, has created complacency  among teaching faculty. On the other  hand, demanding research publication can  add undue pressure and time constraints  on faculty who are already juggling with  teaching, administrative duties, and other  responsibilities. The "publish or perish"  culture can lead to superficial research or  inflated authorship, thereby potentially  lowering the overall quality of research. 1.3 Inadequate teaching faculty Shortage of faculty in many homoeopathic  colleges has led to increased workloads,  reduced research time, and a lack of men torship opportunities for students inter ested in research. There are less number  of teachers available for taking theoretical  classes, imparting practical/ clinical teach ing in OPDs & IPD of hospitals & guid ing other curricular and extra-curricular  activities in the campus. Faculty with in sufficient expertise can lead to a decline in  research quality and productivity, impact ing both individual researchers and the in stitution. Demotivated or less experienced  (in research) faculties are unable to cater  to research needs of students.
Keywords: inadequate research outputs; career advancements; Inadequate logistic support; transportation facilities